Protein quality control and regulated proteolysis in the genome‐reduced organism Mycoplasma pneumoniae. Issue 12 (15th December 2020) - Burgos, Raul; Weber, Marc; Martinez, Sira; Lluch‐Senar, Maria; Serrano, Luis
Abstract: Protein degradation is a crucial cellular process in all‐living systems. Here, using Mycoplasma pneumoniae as a model organism, we defined the minimal protein degradation machinery required to maintain proteome homeostasis. Then, we conditionally depleted the two essential ATP‐dependent proteases. Whereas depletion of Lon results in increased protein aggregation and decreased heat tolerance, FtsH depletion induces cell membrane damage, suggesting a role in quality control of membrane proteins. An integrative comparative study combining shotgun proteomics and RNA‐seq revealed 62 and 34 candidate substrates, respectively. Cellular localization of substrates and epistasis studies supports separate functions for Lon and FtsH. Protein half‐life measurements also suggest a role for Lon‐modulated protein decay. Lon plays a key role in protein quality control, degrading misfolded proteins and those not assembled into functional complexes. We propose that regulating complex assembly and degradation of isolated proteins is a mechanism that coordinates important cellular processes like cell division. Finally, by considering the entire set of proteases and chaperones, we provide a fully integrated view of how a minimal cell regulates protein folding and degradation. SYNOPSIS: A minimal protein degradation machinery required for maintaining proteome homeostasis is defined in the genome‐reduced bacterium Mycoplasma pneumoniae . Genetic and high‐throughput analyses identify substrates and pathways regulated by degradation. All except one of the proteases in M. pneumoniae are essential for cell survival. Phenotypic characterization, protease substrate analysis, and epistasis studies reveal distinct functions for Lon and FtsH, the only two ATP‐dependent proteases in M. pneumoniae . Lon degrades misfolded proteins and unassembled subunits of protein complexes, whereas FtsH regulates the quality control of membrane proteins. Abstract : A minimal protein degradation machinery required for maintaining proteome homeostasis is defined in the genome‐reduced bacterium M. pneumoniae . Genetic and high‐throughput analyses identify substrates and pathways regulated by degradation.